Exploring the current potential of immunotherapeutic-based treatment approaches for the management of oral cancer: An updated review - Abin V. Geevarghese; R. Gopika (Oral Oncology Reports)
One of the most prevalent cancers of the head and neck, oral cancer may seriously hinder eating, represent a danger to life, and impair appearance. The three primary clinical therapies for oral cancer are chemotherapy, radiation, and surgery. However, the primary issues in clinical care are poor therapeutic outcomes and adverse reactions. The tumor microenvironment, or TME, plays a role in prediction in addition to diagnosis, treatment, and avoidance of tumors. It has a direct connection to the growth, development, and migration of tumors. Additional studies on the relationship between the TME and treatment for oral cancer should be performed. This article outlines the traditional approaches for the treatment of oral cancer and immunotherapy, and it ends with an overview of future advances in oral cancer immunotherapy. It is expected that immunotherapy that targets the tumor microenvironment will provide an innovative approach for the beneficial treatment of oral cancer.